Long-term prognostic value of macrophage migration inhibitory factor in ST-segment elevation myocardial infarction patients with metabolic syndrome after percutaneous coronary intervention - Yu, Xiao-Lin; Zhao, Qian; Liu, Fen; Yuan, Yu-Juan; Fang, Bin-Bin; Zhang, Xue-He; Li, Wen-Ling; Li, Xiao-Mei; Du, Guo-Li; Gao, Xiao-Ming; Yang, Yi-Ning (Frontiers in Cardiovascular Medicine, 2022)
Metabolic syndrome (MetS) is a major risk factor for cardiovascular disease and negatively affecting the prognosis of patients with ST elevation myocardial infarction (STEMI). Macrophage migration inhibitory factor (MIF) is a multipotent cytokine involved in various cardiovascular and inflammatory diseases. In this prospective study, we investigate the value of MIF in the long-term prognosis of STEMI combined with MetS after emergency PCI. Circulating MIF levels were measured at admission and major adverse cardio-vascular and cerebrovascular events (MACCE) were monitored during the follow-up period of 4.9 (3.9-5.8) years. MACCE occurred in 92 patients (22.9%), which was significantly higher in MetS (69/255, 27.1%) than in non-MS subgroup (23/146, 15.8%, P<0.05). Patients with MetS developed MACCE had the highest admission MIF level. Kaplan-Meier survival analysis using the cut-off value of admission MIF (143 ng/ml) showed that patients with a higher MIF level had a greater incidence of MACCE than those with lower MIF levels in both MetS group (P<0.0001) and non-MetS group (P=0.016). After adjustment for clinical variables, the value of MIF≥143ng/ml still had the predictive power for MetS group [HR 9.56, 95% CI (5.397 16.944), P<0.001], nevertheless, it was not the case in the non-MetS group. Our findings indicated that MetS is critical risk factor for adverse clinical outcomes in STEMI patients and a high admission MIF level have predictive power for the long-term MACCE, which is superior in STEMI patients with MetS and better than other traditional predictors.